Analysis of Obstetrics & Gynecology Clinic Service Quality with BPJS Patient Satisfaction Level in RAA Soewondo Hospital Pati (Public Health Perspective Journal, 2018)
The quality of health services relates to the level of perfection of health services in causing a sense of satisfaction in each patient, the more perfect the satisfaction, the better the quality of health services. There are 5 dimensions of service quality in assessing service quality including reliability , responsiveness , Assurance, Empathy and tangibles. The still high maternal mortality rate in Indonesia, especially in Pati regency, the government holds a National Health Insurance (JKN) through the Social Insurance Administration Organization Â (BPJS) to address the problem of mortality. This study aims to analyze the service quality of obstetrics gynecology clinics with the level of BPJS patient satisfaction in RSUD Soewondo Pati. This type of research is qualitative with a case study approach. The research sample used purposive sampling technique that is 10 initial informants and developed by snowball sampling technique. The results of the study revealed that most of the informants aged 20 years were 14 people (93.3%), there were 6 high school students (40%) and 11 non-PBI types of BPJS (73.3%).Interview results of Analysis of Obstetric Gynecological Clinic Service Quality with BPJS Satisfaction Level at RSUD RAA Soewondo, from 5 dimensions of service quality obtained results of patients satisfied with service in terms of responsiveness, assurance and empathy as well as in terms of reliability and physical evidence, obtained patient results were quite satisfied with service